Analisis Cemaran Logam Berat Merkuri pada Air dan Udang di Sungai Mandor Kecamatan Mandor Kabupaten Landak - Triana, Linda; Nurjazuli, Nurjazuli; Wahyuningsih, Nur Endah (Jurnal Kesehatan Lingkungan Indonesia, 2012)
Background : Mercury used in gold mining activities in the water of Mandor river in Mandor Disrict of LandakRegency may couse environmental pollution in form of the degradation of water quality and pollution to thebiota, one of them was shrimp. The shrimp living in Mandor river was predicted to be polluted with mercury, andif it was consumed, it may cause health disorders for people, especially those living near the river. This researchhad the objectives of finding out the water Hg content and shrimp Hg content in the Mandor river and finding outthe correlation of water Hg content to shrimp Hg content.Methode : This research was an observing research with the cross-sectional design. The sample collection pointswere at five points with 30 water sample and 30 shrimp samples. The used statistical test was the product mommetcorrelation test.Result : The average of water Hg content was as much as 2,15 ppb ang the average shrimp Hg content was as muchas 0,18 mg/kg. From the test result, the differences in water Hg content showed that there were differences of waterHg content in each research location (p value = 0,001); for shrimp Hg content, there were no different of resultsamong research location except in Kunyit Village and Kopiang Village that showed differences. From the resultsof correlation test, it was found that there was a correlation between water Hg content to shrimp Hg content ( pvalue = 0,047; r = 0,366). The regression result showed the regression coefficient value as much as 0,134 (p value= 0,47); the highest the water Hg content in Mandor river, therefore, the shrimp Hg content will also increase, andwater Hg content influenced on the existence of shrimp Hg content as much as 10,3%. The analysis result ofmercury pollution in Mandor River show that the downstream area has a higher Hg content compared to theupstream area, and the shrimp Hg content increases especially in Mandor Village.Keyword : Hg water, Hg shrimp, Mandor River, Landak Regency